Assessment of Serum FABP‐4 Levels in Hypothyroidism Patients: A Comparative Analysis With a Control Group and Their Correlation With Liver Function Tests and Biochemical Factors - Aldulaimi, Mundher Mohammad Hamzeh; Shafiei, Afsaneh; Ghorbani, Somayeh; Mohammadzadeh, Fatima; Khajeniazi, Safoura (Endocrinology, diabetes & metabolism, 2024)
ABSTRACT Background The association of serum FABP4 and other biochemical‐related parameters is important to determine complications of hypothyroidism. This study aimed to evaluate serum FABP‐4 levels in hypothyroidism patients in comparison with a control group. Materials and Methods Forty‐five patients with hypothyroidism and 45 healthy volunteers were included in this study. Liver function tests, thyroid hormones panel, lipid profile and serum FABP‐4 levels were measured and compared in both groups, and their correlations were analysed. Results Serum FABP‐4 levels were significantly higher in patients with hypothyroidism compared to the control group (p = 0.002), and serum FABP‐4 level in males was higher than it in females (p = 0.022). There was a significant difference between patients with hypothyroidism and the control group in the levels of AST (p = 0.012). Moreover, serum FABP‐4 levels were negatively correlated with age (p = 0.016) and positively correlated with weight (p = 0.044). Conclusion In our study, there was a notable increase in serum FABP‐4 concentration among hypothyroidism subjects. The data suggest that FABP‐4 could potentially be a superior diagnostic indicator for hypothyroidism when contrasted with a control cohort in future studies. The data suggest that FABP‐4 could potentially be a superior diagnostic indicator for hypothyroidism when contrasted with a control. Screening for Hypothyroidism, using FABP4 levels is a novel method which may be used to detect other hypothyroidism‐related diseases.